Peran Asurans Keberlanjutan dalam Memperkuat Transparansi Pengungkapan ESG: Studi pada Perusahaan Publik di Indonesia Tahun 2023–2025 - Sandy Jenfa Utomo; Herlin Tundjung Setijaningsih (Action Research Literate, 2026)
Environmental, Social, and Governance (ESG) disclosure has become a key tool for enhancing transparency among public companies amid growing attention from investors, regulators, and the public regarding sustainable business practices. In Indonesia, sustainability reporting obligations have been strengthened through POJK No. 51/POJK.03/2017 regarding the implementation of sustainable finance for financial service institutions, issuers, and public companies. However, the increasing number of companies publishing sustainability reports does not yet fully guarantee the quality, reliability, and transparency of the ESG information disclosed. This research aims to analyze the role of sustainability assurance in strengthening the transparency of ESG disclosures among public companies in Indonesia during the 2023–2025 period. This study employs a descriptive qualitative approach using literature review and content analysis of regulations, institutional publications, reporting standards, and academic literature related to ESG and sustainability assurance. The research findings indicate that sustainability assurance plays a crucial role in enhancing ESG transparency through independent verification, improving data reliability, strengthening accountability, reducing the risk of greenwashing, and improving companies’ internal control systems. Nevertheless, the effectiveness of sustainability assurance still faces challenges in the form of limited ESG data readiness, variations in assurance standards, audit costs, and companies’ uneven understanding of ESG materiality. This research recommends strengthening ESG data systems, improving the quality of assurance providers, ensuring transparency in the scope of assurance, and preparing companies to meet more integrated sustainability disclosure standards.